Assembly Processes and Co-occurrence Patterns of Abundant and Rare Bacterial Community in the Eastern Indian Ocean - Li, Liuyang; Pujari, Laxman; Wu, Chao; Huang, Danyue; Wei, Yuqiu; Guo, Congcong; Zhang, Guicheng; Xu, Wenzhe; Liu, Haijiao; Wang, Xingzhou; Wang, Min; Sun, Jun (Frontiers in Microbiology, 2021)
Microbial communities are composed of many rare species and a few abundant species. Considering the disproportionately importance of rare species for ecosystem functioning, it is important to understand the mechanisms structuring the rare and abundant components of diverse community in response to environmental changes. Here we used a 16S ribosomal RNA gene sequencing approach to investigate the bacterial community diversity in the eastern Indian Ocean (EIO) during the monsoon and intermonsoon. We employed phylogenetic null model and network analysis to evaluate the assembly processes and co-occurrence pattern of microbial community. We found that higher bacterial diversity was detected in the intermonsoon with high temperature, low Chlorophyll a concentrations and N/P ratios. The balance between ecological deterministic process and stochastic process varied with seasons in the EIO. Meanwhile, conditionally rare taxa (CRT) were more likely modulated by variable selection processes than always rare taxa (ART) and abundant taxa (AT) (CRT > ART > AT). By linking assembly process and species co-occurrence, we demonstrated that the microbial co-occurrence associations tended to be higher when deterministic processes (mainly variable selection) were weaker. And this negative trend was observed in rare species rather than abundant species. The linkage could enhance our understandings of the underlying mechanisms underpinning the generation and maintenance of microbial community diversity.